Ring-Rearrangement Metathetic Approach to Fused 6/5/6/5/6-Oxacyclic Ring System and Bipentalene Derivatives - Kotha, Sambasivarao; Jena, Kunkumita (Synlett, 2022)
We have developed a useful synthetic route to a 6/5/6/5/6-oxacyclic ring system and bipentalene derivatives from dimeric 7-oxonorbornene derivatives by using ring-rearrangement metathesis as a key step. This method provides access to fused oxacycles containing eight stereogenic centers in just three steps and to bipentalene derivatives in two steps only.
Keywords: ring-rearrangement metathesis; oxacycles; pentalenes; norbornenes; Grubbs catalysts